Internalisasi Karakter dalam Kegiatan P5RA Siswa MIN 1 Labuhanbatu - Wina Handayani Br Batubara; Nahriyah Fata (Pusat Riset dan Inovasi Nasional, 2025)
Project Penguatan Profil Pelajar Pancasila dan Pelajar Rahmatan Lil ‘Alamin (P5RA) is an important part of implementing the kurikulum merdeka in Islamic schools. P5RA is expected to be an agent for instilling good character in students. This research aims to illustrate the extent of the effectiveness of P5RA activities as a means of instilling character in students at the primary Islamic school level. Through a qualitative approach, data was collected from observations, interviews, and relevant document studies. The results show that the P5RA project in primary Islamic schools not only sharpens students' life skills but also plays an active role in internalizing character-forming values within them. In each of its projects, there is a value of Rahmatan Lil ‘Alamin targeted for instillation in students through guidance and habituation throughout the project completion process. This applies across all grade levels and phases. These findings highlight the importance of P5RA in character building for students.